ANALISIS ARUS KAS DALAM MENGUKUR KINERJA KEUANGAN PT. UNITED TRACTORS PADA TAHUN 2021-2022 - Junita Nurfaizi; Nasya Soraya Yusuf; Aura Bahrul Safitri; M. Reza Ardiyanto (Akuntansi research UGR, 2023)
The cash flow report is a component of financial reports that has an important role in the decision making process. The cash flow statement includes three main categories: operating activities, investing activities, and maintenance activities. In operational activities, this report reveals how efficient the company is in generating cash from its core business activities. Cash flow statements are used effectively in company performance analysis. The aim of this research is to determine the financial condition of the company PT United Tractors using cash flow ratio analysis. This research was conducted using a descriptive analysis method with a quantitative approach, namely using calculations of the operating cash flow ratio, cash cover ratio, capital expenditure ratio, total debt ratio and net profit ratio. The data collection technique used is document study and literature study. The results of this research as a whole show that the cash flow statement ratio analysis of PT United Tractors in 2021-2022 shows good financial performance.